2020
DOI: 10.5194/bg-2020-422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbon dioxide fluxes and carbon balance of an agricultural grassland in southern Finland

Abstract: Abstract. A significant proportion of the global carbon emissions to the atmosphere originates from agriculture. Therefore, continuous long-term monitoring of CO2 fluxes is essential to understand the carbon dynamics and balances of different agricultural sites. Here we present results from a new eddy covariance flux measurement site located in southern Finland. We measured CO2 and H2O fluxes at this agricultural grassland site for two years from May 2018 to May 2020. Especially the first summer experienced pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Since 2017, sustainable and environmentally friendly field management practices have been conducted at the farm. More detailed information on the location, species, and management practices of Qvidja can be found in Heimsch et al (2021).…”
Section: Measurement Site and Time Rangementioning
confidence: 99%
“…Since 2017, sustainable and environmentally friendly field management practices have been conducted at the farm. More detailed information on the location, species, and management practices of Qvidja can be found in Heimsch et al (2021).…”
Section: Measurement Site and Time Rangementioning
confidence: 99%
“…Focusing the sampling on georeferenced locations and using composite sampling reduces the overall sampling variability and allows tracking relatively small (4 % of background level) changes in SOC stock (Knebl et al, 2015). The offline field measurements at the intensive site Qvidja are described in Heimsch et al (2021).…”
Section: Offline Field and Lab Measurementsmentioning
confidence: 99%
“…The measurement heights fulfill guidelines for grasslands and croplands defined by the Integrated Carbon Observation System (ICOS; Sabbatini and Papale, 2017). For details of the measurement setup in Qvidja, see Heimsch et al (2021).…”
Section: Online Eddy Covariance Measurementsmentioning
confidence: 99%
“…Since the 1970s, global grasslands have been estimated to transition from an anthropogenic sink to a source of anthropogenic GHG (Chang, Ciais, et al, 2015; Chang et al, 2021) due to increased livestock numbers and conversion of natural grasslands to improved pastures, according to a global modelling assessment. Nevertheless, boreal grasslands studies have concluded to either carbon sinks (Heimsch et al, 2021; Kätterer et al, 2011; Poeplau et al, 2015) or sources (Heikkinen et al, 2013; Lind et al, 2020; Lohila, 2004). Thus, a useful avenue of research is to reduce this uncertainty and assess if boreal grasslands are collectively either a net source or sink of CO 2 , both historically and in the future.…”
Section: Grassland Agriculture In the Boreal Regionmentioning
confidence: 99%